A review of changes in the delivery of information to users: 12 years of Literature Reviews in Interlending & Document Supply. Issue 1 (6th July 2015) - McGrath, Mike
Abstract : Purpose: – The purpose of this paper is to consider the changes that have taken place in Interlending & Document Supply over the past 12 years. Design/methodology/approach: – Research of the past 48 literature reviews published in Interlending & Document Supply. Findings: – Over the past 12 years, Interlending & Document Supply has declined dramatically in much of the world, although less so in the US. It is likely to increase in the developing world but not as much as to compensate for the decline elsewhere. Originality/value: – This is the only study that has been made of the changes in document supply in this century.